Better use of caiman yacare carcass and physical-chemical characterization of mechanically separated meat - de Paiva, Gilmar Borges [UNESP]; Bellucci, Elisa Rafaela Bonádio [UNESP]; Trindade, Marco Antônio; Romero, Javier Teles [UNESP]; Barretto, Andrea Carla da Silva [UNESP] (FapUNIFESP (SciELO), 2024)
The captive breeding of the Pantanal caiman (Caiman yacare) offers great potential for the full use of all the component parts of the animal. The meat is an option for human consumption with good sensory acceptance, the skin is valued on the international market and the carcass can be used for obtaining mechanically separated caiman meat (MSCM). This research evaluated the physical chemical parameters of mechanically separated meat obtained from caiman yacare carcass to improve its yield. The proximate composition, lipid oxidation, pH, total volatile bases (TVB) and color during storage under freezing at-18 °C for 90 days were all evaluated. The MSCM presented low lipid content, high protein content and good stability during storage under freezing for 90 days. These results demonstrated that MSCM can be used in the development of caiman meat products.
Melhor aproveitamento da carcaça do jacaré e caracterização físico-química da carne separada mecanicamente
Keywords: exotic meat; innovation; oxidative stability; wild animal